Studi Literatur Pengaruh Pirolisis, Jenis Adsorban serta Aktivator dalam Karakterisasi Asap Cair - Rony Pasonang Sihombing; Keryanti Keryanti; Fitria Yulistiani; Ayu Ratna Permanasari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Liquid smoke is a preservative solution that can be used safely. This grade 1 product can be also used as food preservative. The aim of this article is to discuss and examine the previous experiment’s results by literature review. The outcome of this article is expected to be regenerated by other research using the existing variable which is discussed on this article or using new variable. Based on the result. There are some variables that effect the final quality of liquid smoke. Some of them are pyrolisys temperature, pyrolisys time, adsorbant type and activator type. Pyrolisys temperature used was arround 250 °C – 300 °C with resulted pH 1.41 to 2.25. While for pyrolisys temperature was arround 4 – 5 hours with phenol content arround 3.04% to 4.08%. The type of adsorbant used was zeoilte and quartz sand, which the acid total having both increment and decrement phenomenon. Activator type used were salt activator such as NaCl , NaHCO, CaCl2, Na2SO4 and base activator (NaOH) which producing the most percent acid total.